Disease-modifying antirheumatic drugs in rheumatoid arthritis patients with a history of colorectal cancer - Kleinert, S.; Waldner, Maximilian; Wendler, J.; Kunzmann, V. (Zeitschrift für Rheumatologie, 2016)
Cells of the adaptive immune system are relevant for the anti-tumor immune response; therefore, the basal therapy with disease-modifying antirheumatic drugs (DMARD) in rheumatoid arthritis patients with a history of gastrointestinal cancer must be carefully considered.This article presents the evidence regarding colorectal cancer (CRC) and rheumatoid arthritis.The article is based on a PubMed search as well as a search in congress abstracts of the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR). Current recommendations regarding screening and follow-up of CRC are summarized for clinically active rheumatologists. The current status of therapy and future therapeutic options are presented. The lower incidence of CRC in rheumatoid arthritis (RA) patients and the incidence under treatment with various DMARDs are described. The treatment options for RA patients in different tumor situations, e.g. during cytostatic therapy, palliative and curative situations are discussed, as well as the available evidence. In spite of the unsatisfactory level of evidence, conclusions and practical considerations for use by rheumatologists in clinical practice are discussed.
EVALuna2:2111